Employee Performance Analysis At Regional Secretariat Of Lebong District - Ropi Erwandi; Ida Anggriani; Yudi Irawan Abi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to analyze the performance of employees at the Regional Secretariat of Lebong Regency The sample in this study were 79 civil servants at the Regional Secretariat of Lebong Regency. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing.The results of the multiple regression test show a positive direction with the regression equation Y = 7.321 + 0.183X1 + 0.351 X2 + 0.314X3. Variable X1 (motivation) has a significant effect on Y (performance). This can be seen from the significance value of 0.036 <0.05, so it can be concluded that hypothesis 1 is accepted. Variable X2 (Leadership) has a significant effect on Y (performance). This can be seen from the significance value of 0.000 <0.05. then it can be concluded that hypothesis 2 is accepted. Variable X3 (work environment) has a significant effect on Y (performance). This can be seen from the significant value of 0.000 <0.05, so it can be concluded that hypothesis 3 is accepted. Simultaneous test results then H0 is rejected and Ha is accepted, between the independent variables namely X1 (motivation), X2 (leadership), X3 (work environment), have a jointly significant effect on performance (Y) because of a significant value of 0.000 smaller than 0.05.